Risk factors for latent tuberculosis infection (LTBI) in health profession’s students of the University of Parma - Bonini, Silvia; Riccelli, Maria Grazia; Goldoni, Matteo; Selis, Luisella; Corradi, Massimo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Nowadays Tuberculosis (TB) is one of the major Public Health problems for several professional categories. According to Italian law, University students are compared to workers: the main risk for them is represented by biological risk, in particular by blood-transmitted or by air-transmitted agents. As for TB, many scientific studies demonstrated that prevalence of latent tuberculosis infection (LTBI) in Medicine and Surgery students was lower than those in health workers and in general population. The main aim of this study is the evaluation both of reliability and predictive value of a specific anamnestic questionnaire for previous exposure to Mycobacterium tuberculosis, in order to identify individuals at risk for TB. The Mantoux Tuberculin Skin Test (TST) would be executed to compare results of questionnaire. Methods: The study included Health Profession’s Degrees who were examinated during health surveillance in the period between June 2014 and March 2016. A questionnaire including 10 closed questions was presented to every student. The questionnaire was considerated positive with at least one positive answer. Results: The questionnaire was presented to 580 students, 500 of which completed TST; 466 students were Italian (93.2%). Questionnaire resulted positive in 89 students (17.8%); 15 of them presented positive TST: 14 of them was strangers (93.3%). Sensibility and specificity of questionnaire resulted 100% and 84% respectively. Conclusions: Our data suggested that anamnestic questionnaire could be considerated an efficient mean for identifying candidates for tuberculin screening in a TB- low prevalence population.